An assessment of the health sustainability of sanitation in Ghana: A quantitative analysis. Issue 3 (8th December 2020) - Basiru, Ibrahim; Arkorful, Vincent Ekow; Xu, Yi; Gyekye, Eugene Kwasi; Ibrahim, Abu Hanifa
Abstract : The present study aims to assess the improvements of sanitation system of Kumasi metropolitan area. Sanitation conditions in Africa remain awful with approximately 20% of the population reported to still engage in open defecation in Sub‐Saharan Africa, despite major improvements in other climes of the world. In Ghana, the impacts of poor sanitation systems range from negatively impacting natural resources water quality, to causing health threats to the populations involved. Using health as selected sustainable sanitation, this research assesses reported cases of diseases and deaths associated with unsatisfactory sanitation from 2008 to 2015. Both primary and secondary data were employed. The primary data was collected through interview with key informants by purposive sampling. Quantitative data were analyzed via primary descriptive statistical methods. Results indicate slight improvements in the sanitation system. Our findings suggest that the number of diseases is high due to poor sanitation. However, statistics of deaths are minimal, and these were ascribed to improvements in health care in Ghana. The study has offered recommendations in order to improve sanitation system within the metropolis toward more sustainability. The research is significant because theory developers, researchers, policy makers, and practitioners can make use of its findings to tackle the problems of sustainable sanitation since theories and practices of sustainable sanitation are constantly evolving.